Evaluating Felzenszwalb and Quick Shift Integrated Graph Neural Networks for Monkeypox Blister Segmentation - Satapathy, Ashutosh; Neelima, Duda; Dukka, Naresh (Al-Nahrain Journal of Science, 2025)
The Deep Neural Networks (DNNs) are increasingly leveraged in medical image segmentation, particularly for complex skin conditions like Monkey pox. Due to the distinctive visual features of Monkey pox, such as rashes, blisters, and scabs, distinguishing these features from those of Smallpox and Chickenpox may be difficult, thereby complicating diagnosis. We propose a comparison study with Graph Neural Networks (GNNs) integrated with both Felzenszwalb’s and Quick Shift segment algorithms for Monkey pox blister segmentation. Our GNN and Felzenszwalb’s algorithm combination reached a Mean Structural Similarity Index Metric (SSIM) of 0.85 ± 0.091 and an accuracy of 85.03%, outperforming the other traditional methods. Most distinctly, the combination of Felzenszwalb and GNN were more accurate in segmentation than Quick Shift, which achieved a lower performance SSIM of 0.63 ± 0.080. Correspondingly, GNN using Felzenszwalb’s algorithm reached a lower average test loss of 0.0082 compared to the other approaches. This further establishes that GNNs combined with traditional segmentation methods may greatly enhance accuracy and speed of Monkey pox blister segmentation for improved diagnostic applications. It supports automated lesion analysis for early Monkey pox screening in digital dermatoscopy and teledermatology systems.